Overexpression of Hevea brasiliensis ethylene response factor HbERF‐IXc5 enhances growth and tolerance to abiotic stress and affects laticifer differentiation. Issue 1 (2nd September 2017) - Lestari, Retno; Rio, Maryannick; Martin, Florence; Leclercq, Julie; Woraathasin, Natthakorn; Roques, Sandrine; Dessailly, Florence; Clément‐Vidal, Anne; Sanier, Christine; Fabre, Denis; Melliti, Sémi; Suharsono, Sony; et al.
Summary: Ethylene response factor 1 (ERF1) is an essential integrator of the jasmonate and ethylene signalling pathways coordinating a large number of genes involved in plant defences. Its orthologue in Hevea brasiliensis, HbERF‐IXc5, has been assumed to play a major role in laticifer metabolism and tolerance to harvesting stress for better latex production. This study sets out to establish and characterize rubber transgenic lines overexpressing HbERF‐IXc5 . Overexpression of HbERF‐IXc5 dramatically enhanced plant growth and enabled plants to maintain some ecophysiological parameters in response to abiotic stress such as water deficit, cold and salt treatments. This study revealed that HbERF‐IXc5 has rubber‐specific functions compared to Arabidopsis ERF1 as transgenic plants overexpressing HbERF‐IXc5 accumulated more starch and differentiated more latex cells at the histological level. The role of HbERF‐IXc5 in driving the expression of some target genes involved in laticifer differentiation is discussed.